Suicide is a national security threat - Ng, Alvin Lai Oon * (BusinessToday, 2022)
The recent suicides on the Penang Bridge highlight again the urgency to address such unnecessary deaths that are always one too many. Suicide is a national security threat. With every suicide, there are emotional and financial costs within the family and affected community, reducing the overall productivity of people involved, over a significant amount of time.